Nano-technology platforms to increase the antibacterial drug suitability of essential oils: A drug prospective assessment - Shasank S. Swain; Sudhir K. Paidesetty; Rabindra N. Padhy; Tahziba Hussain (Elsevier, 2023)
A huge number of plant-derived essential oils (EOs) are reported to have lots of ethnomedicinal and biological properties with excellent antibacterial activities. Approximately three hundred EOs (ajowan, anise, basil, camphor, chamomile, clove, citronella, coriander, cumin, eucalyptus, lavender, lemon, orange, peppermint, thyme oils, etc.) are documented under economic class based on commercial and pharmaceutical values. However, most active crude EOs and their constituents like carvacrol, eugenol, geraniol, linalool, thymol, 1,8-cineole, etc. are not found in mainstream drug development modules due to their low solubility, poor bioavailability, and rapid volatility profiles, which reduce their potency, half-life, and pharmacokinetics to achieve the ideal drug-ability profiles. To improve the mainstream use of EOs via nanotechnology, we first gathered more information on plant sources, extraction methods, antibacterial potency with mode of action, and the economic importance of EOs. Further, various nanotechnology platforms, such as nanocarriers, nanoemulsions, liposomes, and cyclodextrins with chemical structure conjugation concept with relevant examples were described. Technically, through optimization in particle size and morphology via a nanotechnology platform, EOs enhance the potency without losing any sensitive properties, easily penetrate and cross the bacterial cell membrane, protect from rapid volatility by coating biocompatible materials, improve the aqueous solubility, improve bioavailability, ensure sustainable release, etc. We hope that the detailed analyses of EOs and nanotechnology platforms will encourage academic and pharmaceutical researchers to use antibacterials by overcoming inadequate drug-ability profiles as potent agents in drugs, food, nutrition, beverages, packaging, and coating materials.